2004
DOI: 10.1017/s0266467403001081
|View full text |Cite
|
Sign up to set email alerts
|

Tropical forest dynamics across a rainfall gradient and the impact of an El Niño dry season

Abstract: Abstract:Tropical forest demography and dynamics were examined in three inventory plots across a precipitation gradient in central Panama. The harsh dry season of 1998 that accompanied the 1997-98 El Niño was spanned by censuses at all three sites. The wet and intermediate plots were similar in total species richness, the dry site somewhat lower in diversity; all three sites differed substantially from each other in species composition. Forest-wide growth of large trees was higher at the wet and intermediate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
229
2
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(249 citation statements)
references
References 42 publications
(58 reference statements)
7
229
2
7
Order By: Relevance
“…10 and 3 implies that mortality rate, , should be directly proportional to rates of limiting resource supply, Ṙ. Several recent field studies appear to support a positive relationship between rates of resource supply and rates of mortality (38)(39)(40)(41). Similarly, our model can be extended to understand how plant metabolism, allometry, and resource supply can influence maximum tree size, total stand biomass, and other ecosystem level processes (see SI Text).…”
Section: Empirical Results and Theoretical Extensionsmentioning
confidence: 76%
“…10 and 3 implies that mortality rate, , should be directly proportional to rates of limiting resource supply, Ṙ. Several recent field studies appear to support a positive relationship between rates of resource supply and rates of mortality (38)(39)(40)(41). Similarly, our model can be extended to understand how plant metabolism, allometry, and resource supply can influence maximum tree size, total stand biomass, and other ecosystem level processes (see SI Text).…”
Section: Empirical Results and Theoretical Extensionsmentioning
confidence: 76%
“…Originally it was not much employed, perhaps because its calculation was quite tedious without a computer [46] (even with the help of Williams's nomograms [21,70]). Nowadays, a is often used to compare communities in terms of species richness, by eliminating the effect of sample size [8,12,13,45,46,50]. In that context, it has shown a strong positive correlation with habitat heterogeneity (expressed in terms of its effect on the fauna) [8,45].…”
Section: Fisher's a As An Index Of Diversitymentioning
confidence: 99%
“…We have chosen to focus on relative species abundance because this is an issue that ecologists have been studying for several decades [23,40,46,70], and that still remains a central theme of ecology [3,12,73]. We can thus benefit from an extensive expertise, and from numerous well established results.…”
Section: Introductionmentioning
confidence: 99%
“…However, longer term studies (without dendrometers) have suggested that on an annual basis the relationship between rainfall and growth might become negative as the average annual rainfall increases. Thus, a four year study in a dry evergreen rainforest of Ghana (Swaine et al 1990;annual rainfall: 570-910 mm, at least eight months with less than 100 mm) found that faster growth occurred during higher rainfall years as expected based on seasonal patterns, whereas studies lasting up to eight years in moist forest sites of Panama (Condit et al 1993a(Condit et al , 2004annual rainfall: 2030-2892.5 to 4.5 months with less rainfall than potential evapotranspiration) found higher growth rates in saplings and several large trees during a drought year, and similarly a six-year study in a wet forest of Costa Rica (Clark and Clark 1992; annual rainfall: 3859 mm, no months with less than 100 mm) found highest median annual growth rates in the smallest and largest size classes during the lowest rainfall years and lowest growth during the highest rainfall years in most of the species studied. Similarly, a short twoyear dendrometer study in a wet evergreen forest of India (Pelissier and Pascal 2000; annual rainfall >4000 mm, five months with less than 100 mm) also showed higher average annual growth during the relatively drier year.…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, a short twoyear dendrometer study in a wet evergreen forest of India (Pelissier and Pascal 2000; annual rainfall >4000 mm, five months with less than 100 mm) also showed higher average annual growth during the relatively drier year. It has been hypothesized for moist forests that increased growth during relatively dry years may be due to reduced cloud cover resulting in increased photosynthetically active radiation Clark 1992,1994;Wright et al 1999;Condit et al 2004) or due to increased atmospheric temperatures during droughts (Condit et al 2004). In this context it is interesting to examine the long term relationship between rainfall and tree growth in the comparatively dry forest of Mudumalai.…”
Section: Introductionmentioning
confidence: 99%